Critérios jurídicos do Supremo Tribunal Federal na construção do acesso à Saúde - Cedenho, Antonio Carlos (2017)
Healthcare, when seen as a subjective right, is a necessary condition for the realization of a fully developed human life, and once it is considered a social right, is a prerogative that coincides with the higher interests of the State. It has become expressly integrated into the roster of fundamental rights and guarantees alongside other social rights in the Constitution of 1988, demarcating the role of the Rule of Law. In this way, it is imposed as a positive right that requires provisions on the part of the State, demanding the realization of tasks – one of them being the concession of medications through public policy – whose very compliance is consubstantial to the right to healthcare. The current research, while inserted into this conjuncture, seeks to identify, analyze, and understand the judicial criteria for the construction of the right to healthcare elaborated within the scope of the Brazilian Supreme Court (STF), judiciary institution and constitutional court, especially in cases of the concession of medications which are not registered by the National Agency for Health Inspection (Anvisa). The significant judicialization of healthcare in recente decades, due to the negative response of the State regarding cases that extrapolate what has been foreseen by public policy and, furthermore, oppose what has been expressly determined by law (article 19-T of Law 8.080/90) indicates the complexity, relevance and urgency of the theme. Upon understanding healthcare as a fundamental right related to citizenship and human dignity, this research seeks to delineate the concept of healthcare and delimit current legal parameters. Starting from this outline, the deficits and challenges that present themselves in the form of metajudicial problems were pointed out and the orientations for the judicial standardization faced with considerable judicialization were presented. Through a selection of judgements issued by the Brazilian Supreme Court that deal with the concession of medication (especially medications not registered by Anvisa), the research aimed to identify and analyze arguments and counter-arguments in order to understand what judicial criteria are currently empolyed in the construction of access to healthcare